Michelle Ann Abate and Gwen Athene Tarbox. Graphic Novels for Children and Young Adults. UP of Mississippi, 2017. - Carlos G Kelly (Studies in 20th & 21st Century Literature, 2017)
Review of Michelle Ann Abate and Gwen Athene Tarbox. Graphic Novels for Children and Young Adults. UP of Mississippi, 2017.
Keywords: Comics; YA Literature; Narrative; Transmedia; Web-based comics